Pre-breeding approaches towards vegetable improvement: A review - Sohi, A; Dogra, B S; Dhiman, S; Pathania, R; Chaudhary, A; Singathiya, P; Ranga, A D; Kumari, A (Plant Science Today, 2025)
The current genetic framework in agriculture poses risks as it undermines global food security. The shift from diverse landraces and local cultivars to genetically uniform modern varieties in traditional agroecosystems has increased the susceptibility of cultivars to pests and diseases. This poses a significant challenge to our valuable biodiversity. In response to changing environmental conditions, there is a need to discover novel genes and traits that enhance adaptability. To create high-yielding cultivars with broader genetic diversity, plant breeders must explore various germplasm sources. Gene banks play an important role in preserving beneficial genes and maintaining genetic variation. The urgent need to expand agricultural germplasm stocks and enhance crop management is beneficial for global food security. Plant genetic resources play a vital role in expanding germplasm stock and improving crop management systems. Pre-breeding delivers the unique advantage of incorporating desired genes from wild germplasm into cultivated varieties, minimizing linkage drag. It focuses on increasing genetic variability among germplasm so that it may be employed in normal genetic improvement programmes for cultivar development. Pre-breeding serves as a beneficial bridge between breeding efforts and genetic resources especially when non-adapted materials are involved. Despite limited utilization of plant genetic resources in crop development programs, pre-breeding can build new genomic technologies to enhance genetic diversity analysis and manipulation with an ultimate approach to create improved cultivars with desirable traits.